Sperm associated antigen 9 (SPAG9) expression and humoral response in benign and malignant salivary gland tumors - Agarwal, Sumit (Oncoimmunology, 2015)
Salivary gland cancers are highly aggressive epithelial tumor associated with metastatic potential and high mortality. The tumors are biologically diverse and are of various histotypes. Besides, the detection and diagnosis is a major problem of salivary gland cancer for available treatment modalities. In the present study, we have investigated the association of sperm associated antigen 9 (SPAG9) expression with salivary gland tumor (SGT). Clinical specimens of benign (n = 16) and malignant tumors (n = 86) were examined for the SPAG9 expression. In addition, the sera and adjacent non-cancerous tissues (n = 72) from available patients were obtained. Our in situ RNA hybridization and immunohistochemistry (IHC) analysis revealed significant difference (p = 0.0001) in SPAG9 gene and protein expression in benign (63%) and malignant tumor (84%) specimens. Further, significant association was also observed between SPAG9 expression and malignant tumors (P = 0.05). A cut-off value of >10% cells expressing SPAG9 protein designated as positive in IHC, predicted presence of malignant SGT with 83.72% sensitivity, 100% specificity, 100% PPV and 83.72% NPV. Humoral response against SPAG9 protein was generated in 68% of SGT patients. A cut-off value of 0.212 OD for anti-SPAG9 antibodies in ELISA predicted presence of malignant SGT with 69.23% sensitivity, 100% specificity, 100% PPV and 78.94% NPV. Collectively, our data suggests that the majority of SGT show significant difference and association among benign and malignant tumors for SPAG9 gene and protein expression and also exhibit humoral response against SPAG9 protein. Hence, SPAG9 may be developed as a biomarker for detection and diagnosis of salivary gland tumors.